THE INFLUENCE OF WAYANG STORY WISDOM VALUES AND TEACHER MOTIVATING BEHAVIOR ON CHARACTER EDUCATION EFFECTIVENESS: THE MEDIATING ROLE OF NEW MEDIA INTERACTIVITY - Kabul Budiono; Soewarto Hardhienata; Suhendra Suhendra (International Journal of Multidisciplinary Research and Literature, 2026)
This study aims to develop and empirically test a structural model examining the influence of wayang story wisdom values and teacher motivating behavior on character education effectiveness, with new media interactivity and value internalization as mediators in vocational high schools. The research employed the POP-SDM-AI method, combining qualitative exploration, quantitative modeling, and optimization. Fifteen public vocational high schools in Indonesia's Banyumas Regency and 164 educators provided their input. Using confirmatory factor analysis, we verified that the instruments we used to measure six aspects of character education wayang values, teacher motivation, material suitability, value internalization, multimedia interactivity, and effectiveness were valid. These variables include wayang values, teacher motivation, material suitability, value internalization, new media interactivity, and the effectiveness of character education. Hypotheses were tested using PLS-SEM with bootstrapping, followed by SITOREM analysis to prioritize improvement indicators. Only the suitability of wayang story materials had a significant direct effect on character education effectiveness (β = 0.197, p = 0.035). Wayang values and teacher motivation showed non-significant direct effects. Neither value internalization nor new media interactivity mediated these relationships (all indirect effects p > 0.05). The model explained only 19.9% of the variance. SITOREM identified the following priority indicators: teacher as a character reinforcer, teacher as a motivator, wayang and honesty values, and national insight. This study provides the first empirical model integrating wayang local wisdom with new media interactivity in a vocational education context, demonstrating that material suitability outweighs the mere presence of values or motivated teachers. The combination of PLS-SEM and SITOREM provides an evidence-based optimization framework for improving character education.